Konstelasi Politik Aceh Pasca MoU Helsinki (2006-2015) - Siti Ikramatoun; Khairul Amin (Sociology Department Of Syiah Kuala University, 2018)
The tsunami disaster in December 2004 was the momentum of Aceh peace which resulted in the Helsinki MoU on August 15, 2005. After that, the political constellation and contestation in Aceh were not dominated by national parties but was influenced by the local dimension, namely the local party and former members of the movement who are involved in practical politics. Political stages as a new means of struggle to realize the ideals of post-peace produce satisfying results, former combatants and local parties succeed in winning Aceh political contestation. its means that the people of Aceh have high expectations to local parties to build Aceh. Thus, the decline of the national party since the 2009 election shows that public trust for the national party is very low. The victory of local parties in political contestation in Aceh would certainly be a signal for national parties to make changes to accommodate local interests and movement's actors in a composition of the party in Aceh.Keywords: Political Constellation, Local Party, Aceh